Spontaneous spawning, ontogeny and growth in captivity of Cynoscion squamipinnis (Perciformes: Sciaenidae). - Abarca, Jorge Boza; Ramírez-Alvarado, Marvin; Barquero-Chanto, Juan; Calvo-Vargas, Emilia; Berrocal-Artavia, Karen (Revista de Biología Tropical, 2016)
The croakers or drums are commercial species, which have been overfished in the Nicoya Gulf, Costa Rica. This study aimed to describe, for the first time, the reproduction and the ontogeny of weakfish, Cynoscion squamipinnis in captivity, in order to perform restocking and mariculture proyects. Wild fish (n= 6, 1-2 Kg) were captured and maintained in the Estación de Biología Marina Juan Bertoglia Richards (Puntarenas, Costa Rica) for a two years period (October 2006- December 2008). During this period, maturation stage was monitored periodically by cannula samples in the females (n= 3) and gentle massage in males (n= 3). All fish were stocked in an 18 t tank, with aeration, 33-35 ups of salinity, and a constant temperature (29 ± 1 °C). The spawning period occurred from January to March 2009, producing 162 000 eggs in three spontaneous spawns. The fertilization percentage was 50-60%, and survival after hatching was 60-85%. The egg diameter was 0.852 mm (Standard deviation (SD)= 0.039), and oil drop of 0.269 mm (SD= 0.016). In the embryonary development, the first mitotic division (MD) was observed one hour after spawning (has), the second MD was 1:30 has, the third MD was 2:00 has, the fourth MD was 2:30 has, and fifth MD at 3:00 has. Morule was observed 3:30 has, the blastule 4:30 has, the gastrule 8:30 has, C shape at 10:00 has, and C shape at 12:00 has. After 19 has hatching larvae occurred. The total length (TL) of the larvae was 2.234 mm (SD= 0.122), and the nothochordial length (NL) was 2.179 mm (SD= 0.119). Preflexion stage was observed 49 has, flexion stage was 11 days after spawn (das) (3.767 mm LT (SD= 0.209)), and postflexion stage was 14 das (4.015 mm LT (SD= 0.302)). After 45 das, the juvenile weights 3.68 g (SD= 1.09). Hatch time of the weakfish larvae was minor than of others croaker species. The stages times of embrionary development were a little different from others croaker species, and probably respond to genetic characteristics of each species and the eggs incubation temperature. The spontaneously spawning without broodstock hormonal applications, and the juveniles production in captivity showed that weakfish is a potential species for restocking programs and mariculture projects.